TRANSPLANTASI ORGAN TUBUH MANUSIA PERSPEKTIF AL-QUR’AN - Lia Laquna Jamali (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2019)
Progress in this modern era resulted in the emergence of the latest breakthroughs in the field of medicine. The new discovery took the form of the practice of organ transplants in humans. This practice is one of the fastest-growing treatments and is an interesting issue in various circles including religion. This is due to the emergence of new problems with a variety of different views. This difference of opinion is due to the opinions of scholars who allow and do not allow, of course, the two arguments have their own reasons. The practice of organ transplants reflects the attitude of helping others as a form of humanity. Because humans are social beings who cannot live alone, each individual needs other. Thus, it awakens the awareness to help each other.